Muhammad ‘Abduh and Ahmad Khan’s Educational and Political Ideas and Activities - Abdul Muis Naharong (Al-Jami'ah: Journal of Islamic Studies, 1990)
“Any Islamic reform now must begin with education, “declares professor Fazlur Rahman in the epilogue of his book, Islam. The importance of education as the prerequisite of Islamic reform was, in fact, also recognized by two 19th century muslim reforms, namely, Muhammad ‘Abduh from Egypt and Ahmad Khan from India. ‘Abduh, who was born in 1849 in a fellah family, recognized the inadequacies of the system of education imparted to muslim students as a result of studying at al-Azhar. The subject taught at this university were only classical Arabic works of dogmatic theology. Moreover, the method of teaching was such that ‘Abduh, recalling his student life, once wrote that the shaykh, in giving lectures, spoke as if he spoke a foreign language. This condition was futher aggravated by the conservative shaykhs who abhorred change and improvement and, therefore, opposed any enlargement of the curriculum of al-Azhar. Ahmad Khan, who was born on 17 October 1817 in a noble family, also paid great attention to the improvement of the system of education prevalent in India. Long before he plunged himself into the services of his people, Ahmad Khan realized the inadequacies of education imparted to Muslims. The madrasahs still used the old system and excluded Western Sciences from their curriculum. Furthermore, there were not many Muslim Students who attended government school and colleges where western sciences were taught. The condition of Indian Muslim reached its lowest ebb after a mutiny broke out in 1857 when the Muslim suffered the most Socially, Economically, and politically. ‘Abduh dan Ahmad Khan, in their attempt to ameliorate the conditions of their respective communities, introduced reforms in various aspects, among which were religious, social, and education reforms. However, being convinced that only through education could the other aspects of their reforms be executed and the conditions of their communities who were under foreign rule be improved, they focused their attention on educational reform. This policy of theirs greatly influenced their political ideas and activities.  This paper will discuss ‘Abduh’s and Ahmad Khan’s educational and political ideas and activities.